2018
DOI: 10.1101/444943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subtraction and division of visual cortical population responses by the serotonergic system

Abstract: Normalization is a fundamental operation throughout neuronal systems to adjust dynamic range. In the visual cortex various cell circuits have been identified that provide the substrate for such a canonical function, but how these circuits are orchestrated remains unclear. Here we suggest the serotonergic (5-HT) system as another player involved in normalization. 5-HT receptors of different classes are codistributed across different cortical cell types, but their individual contribution to cortical population r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…That is, ongoing brain activity (reflecting state‐dependent whole‐brain internal communication processes) and activity evoked by sensory input (reflecting external drive). The results suggest indeed global whole‐brain changes in cortical state induced by 5‐HT input with balanced effects on internal ongoing activity and sensory drive [25,26]. Specifically, we find that 5‐HT1A scales predominantly the weight of internal communication, while 5‐HT2A largely scales the weight of external sensory input.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…That is, ongoing brain activity (reflecting state‐dependent whole‐brain internal communication processes) and activity evoked by sensory input (reflecting external drive). The results suggest indeed global whole‐brain changes in cortical state induced by 5‐HT input with balanced effects on internal ongoing activity and sensory drive [25,26]. Specifically, we find that 5‐HT1A scales predominantly the weight of internal communication, while 5‐HT2A largely scales the weight of external sensory input.…”
Section: Introductionmentioning
confidence: 63%
“…However, could the function of single 5-HT receptor types factually be attributed to distinct and separable effects on either sensory-evoked or internally ongoing activity as our whole-brain model implicates? To address this question experimentally, we used an ePet-Cre mouse line [27] that allowed controlled release of 5-HT by photostimulation of Channelrhodopsin2 expressing 5-HT neurons in the raphe nuclei [25,26]. In parallel we used optical imaging of Ca 2+ fluorescent indicators to track 5-HT-induced modulations of neuronal activity in the visual cortex in vivo (Fig.…”
Section: Gain Matters -Receptor-specific Scaling Of Internal Brain Co...mentioning
confidence: 99%
“…In our study, there also was not meaningful changes in mean membrane potential and mean firing rate of neurons' spontaneous activity before and during electrical stimulation of DRN, which is in agreement with some previous studies (Michaiel et al, 2019). In contrast, some studies reported decreased spontaneous activity in neuronal response by serotonin modulation (Azimi et al, 2018). It was suggested that decreasing gain might decrease the priority of a sensory stimulus (Seillier et al, 2017).…”
Section: -Discussionmentioning
confidence: 97%
“…There is a large topographic organization in the dorsal raphe nucleus (Fiser et al, 2010), so other brain's cortical and subcortical areas are also modulated by serotonergic neuromodulatory neurons, affecting activity in the primary visual cortex (Azimi et al, 2018).…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation